Pengaruh Promosi dan Citra Merek Terhadap Keputusan Pembelian pada Bengkel Mobil Garasi-In - Anwar Fauzi Rohman; Netti Nurlenawati; Dexi Triadinda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of the study was to determine the extent to which the promotion and brand image of the car repair shop influence purchasing decisions. The study used a quantitative method by distributing questionnaires to 97 respondents via Google Form. Data includes instrument analysis to assess validity and reliability, classical assumption tests such as normality tests, heteroscedasticity tests, and multicollinearity tests, hypothesis tests such as t-tests and F-tests, multiple linear regression analysis, and calculating the coefficient of determination. This provides results that promotion and brand image have a significant influence on purchasing decisions. Producing a contribution value of promotion variables and brand image variables to purchasing decisions of 68.8% to purchasing decisions..